Economics of child labour - Khanna, K P (Ed) (New Delhi Deep and Deep, 2001)
The book entitled Economics of child labour has assumed a great importance with the setting up of the WTO and with the developed countries.This book also contain what step can be taken to abolishing child labour,and what role the govt.,the entrepreneurs a
Keywords: Child labor-India; Child labour-Economic aspects; labour policy; Industrial policy